Time to act on diabetes mellitus prevention in the West Bank, oPt: Current and future direct cost of diabetes and its complications. (June 2017) - Abu-Rmeileh, Niveen M.E.; Ghandour, Rula; Mataria, Awad; Awawda, Sameera; Jabr, Samer; O'Flaherty, Martin
Abstract: Aims: To estimate current and future direct cost of diabetes and its complications for the period 2010 and 2030. Methods: This study is a prevalence-based approach that combines model-based forecasts of diabetes prevalence rates from the validated OPT IMPACT Diabetes forecast model, diabetes complications prevalence rates and health care costs and economic data. We use a societal and health care perspective and a time horizon to 2030, and costs were estimated as international US dollar adjusted for Purchasing Power Parity (PPP). Results: The estimated direct costs for diabetes per person in 2012 was 1087 PPP dollars (281-1895 PPP dollar) and the direct costs of diabetes and its complications was 2156 PPP dollar (981-4508 PPP dollar). The estimated diabetes direct cost for the year 2012 was 184 million PPP dollar (47–320 million PPP dollar). The cost is expected to increase to 209 million PPP dollar (54–364 million PPP dollar) in 2015, 248 million PPP dollar (64–432 million PPP dollar) in 2020 and 300 million PPP dollar (77–523 million PPP dollar) in 3030 with 3% discounting rate assumption. The estimated direct cost of diabetes complications is 365 million PPP dollar in 2012, 491 million PPP dollar in 2020 and 595 million PPP dollar in 2030. Conclusions: The burden of diabetes and its complications on the Palestinian health system is huge and actions are needed to address the increasing prevalence of obesity on one hand and providing proper diabetes management on the other hand. Highlights: The prevalence of diabetes and its complication is already high and is expected to be much higher. Estimating the cost of diabetes based on the literature is a quick and informative method. An immediate prevention action is needed to stop the dramatic increase in the prevalence of diabetes.